MEMBANGUN KARAKTER SISWA MELALUI BUDAYA SEKOLAH - Akhmad Riadi (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2018)
The purpose of scientific writing is to find out how to build students' character through school culture. There are several methods used that are qualitative qualifications, in writing the object of wetting is Building Student Character and School Culture. From the results of the discussion in this writing, it can be concluded that it builds the character of students, the involvement of all components of the school, the principal as managerial, teachers, parents and community in the school, in order to realize character education in children, the need for habituation or school culture. which can be implemented through subjects, daily activities, spontaneity activities, extracurricular activities, and other activities. Keywords: Character, School Culture, and Students.